Analysis on the New Development Direction Of Library Materials Based On Knowledge Informatization. Issue 3 (August 2021) - Li, Fengling
Abstract: With the development of information technology, the traditional paper knowledge information has been toward the trend of informatization. Therefore, the library materials information also gradually information zed. This paper first explains the development trend of library in China, and discusses the existing problems and optimization of library information, so as to provide readers with reference.